ASXL1 mutations in AML are associated with specific clinical and cytogenetic characteristics. Issue 10 (3rd October 2018) - Kakosaiou, Katerina; Panitsas, Fotios; Daraki, Aggeliki; Pagoni, Maria; Apostolou, Paraskevi; Ioannidou, Agapi; Vlachadami, Ioanna; Marinakis, Theodoros; Giatra, Chara; Vasilatou, Diamantina; Sambani, Constantina; Pappa, Vassiliki; et al.
Abstract: Mutations of ASXL1 are early events in acute myeloid leukemia (AML) leukemogenesis and have been associated with unfavorable prognosis. In this study, we investigated the type and frequency of ASXL1 mutations in a large cohort of patients with de novo or secondary AML (s-AML) and looked for correlations with cytogenetic findings and disease features. ASXL1 mutations were associated with older age, s-AML and higher peripheral leukocytosis. We observed more frequent co-occurrence of ASXL1 mutations with trisomy 8 and chromosome 11 aberrations but a negative correlation with myelodysplastic syndromes (MDS)-related cytogenetic abnormalities, especially −5/del(5q) and −7/del(7q). ASXL1 mutations were also found in other genetically defined AML subgroups such as those with t(9;22), inv(3)/t(3;3), t(8;21) or t(15;17); however, none of our inv(16) cases carried ASXL1 mutations. We detected two previously unreported ASXL1 mutations, p.IIe593Val and p.Cys688Tyr. Our findings suggest that ASXL1 mutations tend to cluster with specific clinical and cytogenetic profiles of AML patients.